Pengaruh Profitabilitas, Tingkat Pertumbuhan Aktiva, Leverage Operasi, Stabilitas Penjualan terhadap Struktur Modal dan Nilai Perusahaan - Agustin, Kety Lulu; Salim, Ubud; Andarwati, Andarwati (IQTISHODUNA, 2020)
The purpose of this research is to determine the effect of profitability, asset growth, operating leverage and sales stability on the capital structure and firm value. The company value in this study was published with Tobin Q. The population of this study were all manufacturing companies reported on the Indonesia Stock Exchange for the period 2015-2017. In accordance with the selection criteria, there are 46 filtered sample companies. The analysis technique that used is Partial Least Square (PLS). Â The results of hypothesis indicate profitability and sales that are significant to the capital structure while increasing performance and leverage of operations do not have a significant effect on capital structure. Profitability, asset growth, sales stability have a significant effect on firm value while operating leverage does not involve significance to firm value. Profitability and influence of sales have a significant effect on firm value through capital structure, while yield growth and operating leverage are opposite.